The well-crafted argument across the curriculum - White, Fred D.; Billings, Simone J. (Australia Wadsworth Cengage Learning, 2013)
Equips [readers] with the skills to construct meaningful and powerful arguments in various course areas. As it guides you through the process of writing effective arguments, the book covers critical reading strategies, writing, researching, and documenting a topic. You'll find information on drafting and revising arguments, and a variety of composition strategies including freewriting, outlining, and shared reading -- from cover.
Keywords: English language -- Rhetoric -- Problems, exercises, etc; Persuasion (Rhetoric) -- Problems, exercises, etc; Composition (Language arts)